La capacitación administrativa como instrumento de gestión y su incidencia en el desempeño laboral de los servidores de la unidad de gestión educativa local de la provincia de Huamachuco - Monzón Reyes, Tomasa Martina (2017)
In the present investigation a study was performed on the basis of the problem, such as the Administrative Training has an impact on the performance of the workers of the Local Educational Management Unit - Huamachuco, under the assumption that the Administrative Training will bring a positive influence on the performance of the workers of this institution. In this research we applied the descriptive - explanatory design, which had as its purpose the description and interpretation of job performance that is the current reality of the institution, where this allows, describe relationships between two variables at a given time. The population was composed of 154 servers in the Local Educational Management Unit - Huamachuco, in this opportunity took the sample of 49 servers, who are the ones who are more perennial in their centers of work who are unable to apply the survey, the results of which passed through a statistical analysis. The results show a highly favorable influence on the part of the UGEL - Huamachuco, in relation to the implant and training as part of the development of norms of the activities of this institution and therefore validate the advantages that this would have to improve the job performance of each of the servers.